A multi‐stage analysis of antecedents and consequences of knowledge management evolution. Issue 1 (2014) - Hsiu‐Fen Lin
<x xml:space="preserve"> Abstract </x> Purpose – Drawing from knowledge‐based view and balanced scorecard approach, this study seeks to develop an integrative model to examine the influence of two knowledge management (KM) strategies, codification KM strategy and personalization KM strategy, on the multi‐stage KM evolution (KM adoption, implementation and institutionalization stages), which in turn affects balanced scorecard outcomes (financial performance, internal process performance, customer performance, and growth and learning performance).Design/methodology/approach – Survey data from 244 managers (currently and directly in charge of KM activities) in large Taiwanese firms were collected and used to test the research model using the structural equation modeling (SEM) approach.Findings – The results have revealed that both the codification KM strategy and personalization KM strategy are positive factors for stage‐based KM evolution, but their relative importance differs across the three subsamples. Additionally, the results showed that the internal process and customer perspectives play a critical role in measuring performance during the earlier stages of KM evolution, while the financial and learning and growth perspectives emphasize the performance achievements from the latter stages.Practical implications – Since KM implementation is an evolutionary process, using both financial and non‐financial measures to assess organizational performance through KM efforts, such as the four balanced scorecard perspectives, can take full advantage of stage‐based KM evolution. The results indicate that the time‐lag effect is critical to distinguishing different forms of organizational performance.Originality/value – Theoretically, this study aims to provide a research model that is capable of understanding the antecedents and consequences of staged‐based KM evolution. From a managerial perspective, the findings of this study provide valuable guidelines to policy‐makers and practitioners in accelerating KM evolution and achieving organizational performance. <ack> <x xml:space="preserve"> Acknowledgements </x> Received 23 July 2013 Revised 9 November 2013 Accepted 11 November 2013 </ack>